Effects of Bakuchiol on chondrocyte proliferation via the PI3K‐Akt and ERK1/2 pathways mediated by the estrogen receptor for promotion of the regeneration of knee articular cartilage defects. (12th August 2019) - Xu, Kang; Sha, Yongqiang; Wang, Sixiang; Chi, Qingjia; Liu, Yanju; Wang, Chunli; Yang, Li
Abstract: Objectives: Cartilaginous tissue degradation occurs because of the lack of survival of chondrocytes. Here, we ascertained whether bakuchiol (BAK) has the capability of activating chondrocyte proliferation. Materials and methods: The effect of BAK on the proliferation of rat chondrocytes at a concentration of 10 and 20 µmol/L was investigated. The molecular mechanisms involving target binding and signalling pathways were elucidated by RNA‐sequencing, qPCR, molecular docking and Western blotting. Matrigel mixed with bakuchiol was implanted locally into rat knee articular cartilage defects to verify the activation of chondrocytes due to bakuchiol in vivo. Results: Bakuchiol implantation resulted in the activation of rat chondrocyte proliferation in a dose‐dependent manner. RNA‐sequencing revealed 107 differentially expressed genes (DEGs) with 75 that were up‐regulated and 32 that were down‐regulated, indicating increased activation of the PI3K‐Akt and cell cycle pathways. Activation of the phosphorylation of Akt, ERK1/2 and their inhibitors blocked the proliferative effect of bakuchiol treatment, confirming its direct involvement in these signal transduction pathways. Molecular docking and siRNA silencing revealed that estrogen receptor‐α (ERα) was the target of bakuchiol in terms of its cell proliferative effect via PI3K activation. Two weeks after implantation of bakuchiol, the appearance and physiological structure of the articular cartilage was more integrated with abundant chondrocytes and cartilage matrix compared to that of the control. Conclusions: Bakuchiol demonstrated significant bioactivity towards chondrocyte proliferation via the PI3K‐Akt and ERK1/2 pathways mediated by estrogen receptor activation and exhibited enhanced promotion of the remodelling of injured cartilage.